Associations between statins and adverse events in primary prevention of cardiovascular disease: systematic review with pairwise, network, and dose-response meta-analyses - Cai, T; Abel, L; Langford, O; Monaghan, G; Aronson, JK; Stevens, RJ; Lay-Furrie, S; Koshiaris, C; McManus, RJ; Hobbs, FDR; Sheppard, JP (BMJ Publishing Group, 2021)
Objective To assess the associations between statins and adverse events in primary prevention of cardiovascular disease and to examine how the associations vary by type and dosage of statins.